Sequencing the Exon.4 of the LDL Receptor Gene in Patients with Familial Hypercholesterolemia in the Population of Bushehr, Southwestern Iran: the Possible New Mutations - Shima Parviz; Seyed Javad Hosseini; Ali Movahed (Journal of Advanced Biomedical Sciences, 2021)
Background & Objective: Familial hypercholesterolemia (FH) is the most common genetic disease in the world and an autosomal dominant disease characterized by increased plasma cholesterol and low-density lipoprotein (LDL) concentrations. The clinical diagnosis of the disease is based on family history, the findings of medical examinations, and the measurement of cholesterol levels. The most important cause of FH is the mutation in one of the LDL-R, APOB, and PSCK9 genes. About 90% of mutations occur in the LDL-R gene, which accounts for a total of 2,000 different mutations. Different types of mutations have been observed on different exons of the LDL-R gene, but most of the mutations have been reported on Exon 4. The aim of this study was to sequence and analyze Exon 4 in patients with familial hypercholesterolemia in Bushehr province in Iran. Materials & Methods: In this study, 32 patients were selected based on global criteria for diagnosing the disease, and a portion of LDL-R containing complete sequence of exon 4 was amplified using LDLRE4F1/ LDLRE4R1 Primers and blood genomic DNA as a template. PCR products were sequenced and compared with reference sequence to find probable mutations. Results: The results of sequencing and comparison with the reference sequence showed that no mutation was found in the exon 4 LDL-R gene. Therefore, this exon did not play a role in FH in the population under study. Conclusion: Therefore, the cause of FH may be due to the mutations in other areas of the LDL-R gene or other genes, such as APOB and PSCK9.